Working capital management in the food industry: a comparison of cash conversion cycles along the value chain and their impact on profitability - Poeschel, Felix Maximilian Leopold (2022)
This Work Project aims to identify diversity in working capital management of companies in the food value chain. It also investigates how working capital management affects profitability of different value chain stages. Based on a sample of 194 companies of the subindustries Agricultural Products, Packaged Foods & Meats, and Food Retail, this study found different working capital management patterns across the value chain. Furthermore, shortening cash conversion cycle does not, as a rule, improve profitability. However, working capital management levers can be used to increase profitability, depending on the value chain stage in which a company operates.